Variability in Morpho-physiology, Tuber Yield and Starch Content of Several Arrowroot Populations in Garut District - Asep Rohandi; Budiadi Budiadi; Suryo Hardiwinoto; Eni Harmayani; Dede J. Sudrajat (AGRIVITA, Journal of Agricultural Science, 2017)
Arrowroot (Maranta arundinacea L.) is an important starchy plant which has potential utilization for food,industry and medicine. The study was undertaken to assess the variability in morpho-physiological characters, tuber yield and starch content of 23 arrowroot populations in Garut District, West Java. The result showed some significant differences in morpho-physiological characteristics, tuber yield and starch content. Growth characteristics revealed that Cilawu population recorded the highest values for some characters: high, leaf number, above growth biomass and tuber biomass. Cikajang population showed the highest tuber yield (210.6 g per plant) followed by Cilawu population (134 g per plant). Cikajang and Cilawu populations also provided the highest tuber biomass, 46.6 g and 60.0 g respectively. Cilawu population was a second population producing the highest starch content (26.1 %) after Cibatu population (27 %). The higher heritability coupled with genetic advance revealed for fresh tuber yield indicated that selection on basis of the character may be helpful to improve arrowroot yield. Most of the growth characteristics had not significant correlation indicating that the characteristics are not good indicator for selection. Cilawu, Cikajang and Cibatu populations have good potential to produce the high quality and quantity of tuber for arrowroot cultivation in Garut District.